Relation between Body Mass Index and Severity and Mortality of COVID-19 Patients at RSU Haji Surabaya - uswatun hasanah (Majalah Farmaseutik, 2022)
COVID-19 is a new disease that emerged and was recognized in December 2019. This disease causes massive deaths in countries around the world, so the WHO has declared it a global pandemic. The increase in death cases due to COVID-19 is also felt in Indonesia. Until February 2022, the number of deaths was recorded at 3.30%, higher than the world's cases of death at 2.3% and the WHO 1.50%. The increase in body mass index can affect the clinical condition of the patient, including the severity of the case to death in the patient. Patients with an increased BMI were identified as a risk factor for the severity and death of COVID-19 patients. The purpose of this study was to determine the relation between BMI and the severity and mortality of COVID-19 patients. The research method used a retrospective cohort conducted on COVID-19 in patients at RSU Haji Surabaya for the period March 2020 to March 2021. Data analysis in assessing the relation between variables was calculated using the Chi-square test with a significance value (p<0.05). The results of research conducted at RSU Haji Surabaya showed that there was no relation between body mass index and case severity (p=0.065) and there was a significant relation between BMI and patient mortality (p=0.014). The conclusion is that COVID-19 patients with less or more BMI can increase the severity and mortality.